Gambaran Perkembangan Anak Usia Prasekolah Di TK Islam Futuhiyyah Doro - Umarina Umarina; Ratnawati Ratnawati (OBAT: Jurnal Riset Ilmu Farmasi dan Kesehatan, 2024)
Background: as we know every child will experience a period of growth and development. The growth and the development could be seen from some aspects such as: language, fine motor skills, gross motor skills, social personal aspects. This period is sensitive one; the children will be sensitive to receiving all stimuli given by their parents or their environment. The study aims to obtain the description of the development of preschool age children at the Futuhiyyah Doro Islamic Kindergarten.Method: it is a quantitative descriptive with a total sampling technique as the technique of data collecting; 82 respondents. The instrument applied was the Pre-Developmental Screening Questionnaire as the development measuring tool. Besides, the data analysis used was univariate in the form of a percentage frequency distribution.Results: the result stated characteristics of preschool age children at the Futuhiyyah Doro Islamic Kindergarten are the average age is 68 months, 47 respondents (57.3%) were female and 35 (42.7%) were male. Furthermore, at that age, there were 72 respondents (87.8%) who had appropriate development and 10 respondents (12.2%) who doubted it.Conclusion: Description of the development of preschool age children at the Futuhiyyah Doro Islamic Kindergarten, there were 72 respondents (87.8%) with appropriate development.